An investigation into the effects of socio-economic and education factors on WAIS-III performance in a stratified South African sample - Kemp, Ryan (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
The present study examined the effects of socio-economic status, quality and level of education on performance on the Wechsler Adult Intelligence Scale 3rd Edition r.:w AIS-III). The study was conducted within the context of the present Human Sciences Research Council (HSRC) W AIS-III standardisation process, cross-cultural psychometric research and the notion of test-wiseness. A South African sample (N = 68) comprising African first language (n = 40) and English first language (n = 28) participants, stratified for age (19 - 30 years), gender and educational attainment (Matric and Graduate) were utilised. Effects due to quality of education were determined by dividing the African language participants into those with private/model C schooling (n = 20) and those with DET schooling (n = 20). Effects due to level of education were determined by dividing the entire sample into those with Matric level education (n = 34) and those with Graduate level education (n = 34). Detailed demographic and socio-economic information were recorded for all participants, who completed the entire American version of the W AIS-III. Results revealed a highly significant positive correlation between high socio-economic status and W AIS-III Full Scale IQ. In addition the respective impact of the relatively poor quality of education and lower level of educational attainment on W AIS-III performance was substantial. These results were discussed in terms of their implications for cross-cultural research, the HSRC standardisation of the W AIS-III and the practical use of the W AIS-III in neuropsychological assessment.
Keywords: Wechsler Adult Intelligence Scale -- South Africa; Intelligence tests -- South Africa